Childcare, Single-Mother Sex Workers, and Islamic Family Law: Contemporary Realities Between Child Welfare and Social Stigma - Aditya Ramadhan; Roqiyul Ma’arif Syam; Afif Muamar; Nazula Alfirahmah; Dede Al Mustaqim (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose – Contemporary Ḥaḍānah practices are often confronted with complex social and economic realities. Childcare practices by Single mothers working as sex workers must bear full responsibility for childcare amid economic pressures and moral stigma. This study focuses on the tension between the principle of child welfare and the social marginalization of single mothers who are sex workers. Design/methods/approach – This research employs a qualitative field method with a case study. Primary data were collected through in-depth interviews and observations of four single mothers who worked as sex workers in Astana Village, Cirebon, Indonesia. The data were analyzed thematically using the interpretive framework of Qirā’ah Mubādalah and Maslow’s hierarchy of needs. Findings – The research findings show that the practice of ḥaḍānah by single sex worker mothers in Astana Village, Cirebon, Indonesia reflects a reciprocal caregiving relationship oriented towards the welfare of the child, as emphasized in the Qirā’ah Mubādalah perspective. Analysis using Abraham Maslow's Hierarchy of Needs Theory reveals that caregiving is carried out simultaneously and contextually through the fulfillment of physiological needs, safety, affection, and even the child's future aspirations, despite structural limitations. Research implications/limitations – These results confirm that the suitability of ḥaḍānah cannot be measured by the stigma of the mother's work but rather by her commitment and ability to fully meet the needs of her children. Originality/value – This research offers a novel interdisciplinary analysis integrating Qirā’ah Mubādalah and Maslow’s theory to reinterpret maternal resilience and justice in childcare, promoting a more compassionate and contextual understanding of Islamic family law.